PERAN KEBIJAKAN DIVIDEN SEBAGAI MEDIATOR DALAM HUBUNGAN PROFITABILITAS DAN LIKUIDITAS TERHADAP RETURN SAHAM PADA SEKTOR PERBANKAN - Sanu, Apri Alson; Amtiran, Paulina Y.; Arthana, I Komang (Universitas Nusa Cendana, 2025)
This study analyzes the effect of profitability and liquidity on stock returns, with dividend policy as a mediating variable in banking companies listed on the IDX for 2021-2023. Profitability is measured by ROA and ROE, liquidity by CR, dividend policy by DPR, and stock returns based on price changes. The study applies linear regression analysis and Sobel mediation test, using secondary data from 15 companies selected through purposive sampling, resulting in 45 observations. The findings indicate that ROE positively affects dividend policy, while ROA has no significant impact. Liquidity negatively affects dividend policy, suggesting that firms with high liquidity tend to retain earnings. ROE positively influences stock returns, while ROA has a negative impact. Liquidity and dividend policy do not significantly affect stock returns. Dividend policy does not mediate the effect of ROA and ROE on stock returns but significantly mediates the relationship between liquidity and stock returns. This study suggests that investors prioritize equity-based profitability, while management should balance liquidity and dividend policies to maintain company attractiveness